The degradation behaviour, residue distribution, and dietary risk assessment of malathion on vegetables and fruits in China by GC-FPD. (January 2020) - Liu, Yiping; Liu, Shuangqing; Zhang, Ya; Qin, Dongmei; Zheng, Zuntao; Zhu, Guangyan; Lv, Yuntao; Liu, Zhaoqing; Dong, Zhe; Liao, Xiaolan; Li, Xiaogang
Abstract: The gas chromatography-flame photometric detector (GC-FPD) was used to detect malathion residues content in vegetables (cherry tomatoes and broccoli) and fruits (mulberries, cranberries, and figs). The recoveries of samples were 76.2 ± 3.5%–103.9 ± 3.6% at a spike level of 0.01–10 mg/kg, the relative standard deviation (RSDs) were 2.1%–7.3%, and the limit of quantification (LOQs) were 0.01–0.02 mg/kg. On the basis of the normative field trials, the degradation half-life of malathion were 1.10–2.15 days, which indicated that malathion degrades quickly. The final distribution of malathion residues in various vegetables and fruits varied from <0.01 to 0.58 mg/kg. The long-term dietary risk assessment results showed that the national estimated daily intake (NEDI) of malathion in various populations of China ranged from 0.000021 to 0.000549 mg/kg bw, and the risk quotient (RQ) ranged from 0.007% to 0.183% and were less than 100%, which indicated that malathion has a low risk for long-term dietary intake these crops. The maximum residual limits (MRLs) of malathion can be set as 1 mg/kg for cherry tomatoes, broccoli, mulberries, cranberries, and 0.2 mg/kg for figs, respectively. These results would be considered as important references for monitoring and assessing the quality safety of agricultural products and protecting consumer health. Graphical abstract: Image 1025511